2017
DOI: 10.1245/s10434-017-6109-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Limb Perfusion and Infusion for Extremity Soft Tissue Sarcoma: A Contemporary Systematic Review and Meta-Analysis

Abstract: ILP and ILI for extremity STS can be safely performed with appreciable response rates and significant limb salvage rates. Further study is needed to identify optimal treatment regimens by histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 48 publications
2
41
0
7
Order By: Relevance
“…Comparing ILP/ILI patients diagnosed with melanoma to those with STS, the melanoma patients were slightly older (mean 64 years for melanoma and 59 years for STS), consistent with previous reports of age at the time of procedure for each disease . The mean LOS (4.8 days) following ILP/ILI for melanoma in the current study was most consistent with what is reported in the literature for ILI .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Comparing ILP/ILI patients diagnosed with melanoma to those with STS, the melanoma patients were slightly older (mean 64 years for melanoma and 59 years for STS), consistent with previous reports of age at the time of procedure for each disease . The mean LOS (4.8 days) following ILP/ILI for melanoma in the current study was most consistent with what is reported in the literature for ILI .…”
Section: Discussionsupporting
confidence: 89%
“…The overall response (OR) rates achieved with ILP are as high as 70%‐90% and complete response (CR) rates up to 60%‐70% . Both methods of regional therapy were subsequently used for patients with locally advanced STS with similar OR rates, but typically lower CR rates ranging from 18%‐30% …”
Section: Introductionmentioning
confidence: 99%
“… When possible, ILP can be used in a neoadjuvant manner (preoperative) to reduce the dimensions of the primary tumor or improve local conditions, increasing the probability of limb preservation surgery 61 . However, alpha and melphalan NTT are unavailable in most centers in Brazil; thus, we do not recommend this type of treatment outside of institutional protocols with experienced surgeons (IIC) 62 …”
Section: Management Of Local/localized Disease (See Figure 1)mentioning
confidence: 99%
“…61 However, alpha and melphalan NTT are unavailable in most centers in Brazil; thus, we do not recommend this type of treatment outside of institutional protocols with experienced surgeons (IIC). 62…”
Section: Recommendationmentioning
confidence: 99%
“…Interestingly, although the Peritoneal Cancer Index (PCI) score was predictive of ability to cytoreduce, it did not predict survival for patients with high-grade appendiceal or endometrial carcinoma. Wright et al 16 18 In addition, a meta-analysis on the role of isolated limb infusion (ILI) for sarcomas presented by Neuwirth et al 19 demonstrates a complete response rate of 26%. This comprehensive analysis of regional therapies used for the limb is the result of collaboration, science, and persistent efforts at centers of excellence.…”
mentioning
confidence: 99%